Pokolenie Niewiasty / Dariusz M. Kaczmarczyk. - Kaczmarczyk, Dariusz M. (1971- ).
1. Ap 12, 17. 2. Maryja Kościołem. 3. Maryja Matką Kościoła. 4. Golgota. 5. Zesłanie Ducha Świętego. 6. Wielki znak w historii.